Fear and hoping in the Arctic:Charting the emotional fabric of resource extraction - Lempinen, Hanna; Lindroth, Marjo (The Extractive Industries and Society, 2021)
Natural resources play a prominent role in the future development plans of many Arctic societies. The extraction of these resources is promoted as the foundation for future development and well-being. Arguments opposing envisioned resource developments are often rejected as emotional and irrational, which both downplays and underlines the weighty role that affects play in resource debates. It also masks the ways in which affects are not politically neutral but strategically encouraged, muted or overlooked. In this article, we focus on the sidelined affective dimension of resource debates through two cases from the Euro-Arctic region: planned energy development in the Barents Region and envisioned mining projects in Greenland. Through these cases and our engagement with the emerging literature on resource affects, we highlight the important role of emotions in (envisioned) resource extraction projects. Our discussion of the Barents Region's energy potential and independence-aspiring Greenland demonstrates the presence of versatile affective states – hope, expectation, prestige and redemption entangled with worry, fear and anxiety – that bear a great resemblance across different resource contexts. We draw attention to the diversity of emotions at play in development plans and to the ways affect can be exploited for political purposes.